The Chaplin collection Vol. 1. - Chaplin, charlie, 1889-1997. (Burbank, CA : Warner Home video and MK2, 2003)
A master filmmaker and comic genius rolled into one, Charlie Chaplin set a standard for comedy that has inspired artists for over 70 years. This set is an example of Chaplin and his trademark at their best.
The great dictator (1940) + special features (120 min.) -- Limelight (1952) + special features (132 min.) -- Modern times (1936) + special features (83 min.) -- The gold rush (1925) + special features (69 min., 96 min.).
DVD release of 10 Chaplin motion pictures.
Charlie Chaplin.
DVD
Keywords: Silent films; Comedy films; Short films